Scientific Integrity in Medicine and Surgery - Haro-Haro, Daniel Enrique (2022)
We review scientific integrity in medicine and surgery with an emphasis on good conduct in all research and the promotion of a culture of values and principles to apply them to scientific work. We review questionable practices in medical research, including plagiarism that puts at risk the value of honesty and respect for the scientific production of others.